Pathways from parental AIDS to child psychological, educational and sexual risk: developing an empirically-based interactive theoretical model. - Cluver, L; Orkin, M; Boyes, M; Sherr, L; Makasi, D; Nikelo, J (Elsevier, 2013)
Increasing evidence demonstrates negative psychological, health, and developmental outcomes for children associated with parental HIV/AIDS illness and death. However, little is known about how parental AIDS leads to negative child outcomes. This study used a structural equation modelling approach to develop an empirically-based theoretical model of interactive relationships between parental or primary caregiver AIDS-illness, AIDS-orphanhood and predicted intervening factors associated with children's psychological distress, educational access and sexual health. Cross-sectional data were collected in 2009-2011, from 6002 children aged 10-17 years in three provinces of South Africa using stratified random sampling. Comparison groups included children orphaned by AIDS, orphaned by other causes and non-orphans, and children whose parents or primary caregivers were unwell with AIDS, unwell with other causes or healthy. Participants reported on psychological symptoms, educational access, and sexual health risks, as well as hypothesized sociodemographic and intervening factors. In order to build an interactive theoretical model of multiple child outcomes, multivariate regression and structural equation models were developed for each individual outcome, and then combined into an overall model. Neither AIDS-orphanhood nor parental AIDS-illness were directly associated with psychological distress, educational access, or sexual health. Instead, significant indirect effects of AIDS-orphanhood and parental AIDS-illness were obtained on all measured outcomes. Child psychological, educational and sexual health risks share a common set of intervening variables including parental disability, poverty, community violence, stigma, and child abuse that together comprise chain effects. In all models, parental AIDS-illness had stronger effects and more risk pathways than AIDS-orphanhood, especially via poverty and parental disability. AIDS-orphanhood and parental AIDS-illness impact child outcomes through multiple, interlinked pathways. The interactive model developed in this study suggests key areas of focus for interventions with AIDS-affected children.